Marine Natural Products: New Avenue in Treatment of Osteoporosis - Chaugule, Sachin R.; Indap, Madhavi M.; Chiplunkar, Shubhada V. (Frontiers in Marine Science, 2017)
Bone metabolism is a physiological process that maintains the skeletal integrity and bone functions. Skeletal integrity is always balanced by two key cell types- bone resorbing osteoclasts and bone-forming osteoblasts. Imbalance between generation and function of osteoclasts and osteoblasts often leads to pathological conditions such as osteoporosis, osteopetrosis, Paget's disease. Osteoporosis is one of the most common age-related diseases characterized by decreased bone mineral density and microarchitectural deterioration. Current therapies are indeed effective in preventing bone loss but are also followed by side effects. Since many years, marine organisms have been considered as a good source of bioactive molecules or compounds with potential pharmaceutical properties. Marine natural products derived from various marine resources such as marine cyanobacteria, dinoflagellates, algae, sponges, soft corals, molluscs, fishes, and mangroves had shown profound effect on bone metabolism through inhibiting osteoclastogenesis and up-regulating osteoblastogenesis via modulating RANK/RANKL/OPG pathway. Amongst the pre-clinically investigated marine natural products for management of osteoporosis, very few are under phase I clinical trials. This review discusses the currently available pharmacological drugs and there major health concern in osteoporosis treatment. It further gives an insight into various marine resources and marine-derived bioactive products, depicting their mechanism of action, functional role and how these can be exploited for the treatment of osteoporosis.